Artificial neural networks - Schalkoff, Robert J. (McGraw-Hill series in computer science. / Artificial intelligence, 1997)
Artificial Neural Networks brings together an identifiable core of ideas, techniques, and applications that characterize this emerging field. The text is intended for beginning graduate / advanced undergraduate students as well as practicing engineers and scientists.